TAX-DEDUCTIBLE EXPENSES ADJUSTMENT AND FAILURE TO PAY - PRACTICAL APPLICATION AND TAX OPTIMISATION POSSIBILITIES IN POLAND - J. Szlęzak-Matusewicz (Финансы: теория и практика)
Reduction of payment backlogs issuing from failure to pay or from too long maturity dates was assumed to be effected by some provisions of the Act on the reduction of some of the administrative burden in the economy, introducing, among other things, Art. 15b of the Corporate Income Tax Act in Poland. An aim of the considerations carried out in this article is to present the rules concerning adjustment of tax-deductible expenses and to exhibit that in the reality those regulations are a source of tax risk and cause aggravation of the financial situation of taxpayers (not only debtors). In effect, these regulations are a further instrument of the growth of budgetary revenues.